lncRNA OR3A4 Promotes the Proliferation and Metastasis of Ovarian Cancer Through KLF6 Pathway - Guo, Fangfang; Du, Jianan; Liu, Lingling; Gou, Yawei; Zhang, Mingming; Sun, Wei; Yu, Hongmei; Fu, Xueqi (Frontiers in Pharmacology, 2021)
Abstract Aims Ovarian cancer is a joint malignant tumor of the female reproductive system in clinical. Some clinical studies have shown that OR3A4, which is a cancer-causing lncRNA that plays an important role in promoting the occurrence and development of tumors in a variety of tumors. And we also felt that it expressed in ovarian tissue. However, the function of OR3A4 in ovarian cancer remains unclear. Methods and results To further verify the function of lncRNA OR3A4 in ovarian cancer. We established the xenograft model in zebra fish. In this study cell transformed with OR3A4 shRNA plasmid were transplanted into the zebra fish and the cell proliferation and migration ability were significantly reduced compared to the empty vector. While knocking out OR3A4, we further down-regulated its expression by siRNA of KLF6. Our study found that knocked out OR3A4 resulted in a decrease in cell proliferation and migration level, which can be found by down-regulated the expression of KLF6. We also verify the relationship between OR3A4 and circulating in zebra fish xenograft model, the results indicate that lncRNA OR3A4 may be involved in the resistance of ovarian cancer to complain. Conclusion lncRNA OR3A4 promotes the proliferation and metastasis of ovarian cancer through KLF6 pathway.